The Shifting Balance of Grasslands, Shola Forests, and Planted Trees on the Upper Nilgiris, Southern India - Noble, William A. (Indian Forester, 1967)
By studying upper Nilgiri vegetation in southern India additional understanding may be gained of: (1) man's contribution to tropical temperate grassland formation; (2) recent afforestation as proof that Nilgiri grasslands with support tree growth; and (3) possible future areal proportions of grasslands, indigenous forests called sholas, and planted foreign trees on the Nilgiris plus other southern Indian massifs. Annual fires set by pastoralists for hundreds and possibly thousands of years have slowly extended grasslands. Rolling upper Nilgiri terrain, aiding fire spread, has contributed to the process. Surface configuration and frequency of burning have been responsible for differences between interfluvial, denaritic, and patch sholas. Felling trees for domestic necessities and to clear land for agriculture doubtlessly speeded up grassland formation. Through grazing by Toda buffaloes and periodic fires, plots once utilized by Badaga farmers may become grasslands within a decade. Archaeological evidence indicates that members of a megalithic culture possible lived in the area centuries immediately before and after 1 A.D., and were farmers and livestock rearers. Thus, the more rapid process may have been operative for over 2,000 years. That trees will readily grow on temperate Nilgiri grasslands is proven by thousands of former grassland acres afforested with imported Australian acacias plus eucalypti, and by the conversion of the Ootacamund city area from predominantly grasslands to forest in approximatety fifty years. In the future, grassland and shola acreages may well decrease, while cropped lands and tracts planted with imported trees increase. Dominating tree species on the upper Nilgiris might ultimately be acacias and eucalypti.